PENGARUH PEMBERIAN KOMPRES HANGAT TERHADAP PENURUNAN NYERI PUNGGUNG PADA IBU HAMIL TRIMESTER III DI WILAYAH KERJA PUSKESMAS PACEDA KOTA BITUNG: THE EFFECT OF GIVING WARM COMPRESSES ON REDUCTION BACK PAIN IN PREGNANT WOMEN IN THE THIRD TRIMESTER IN THE WORKING AREA OF THE PACEDA HEALTH CENTER BITUNG CITY - Irma M. Yahya; Sarwan; Andini P. Napu (Intan Husada : Jurnal Ilmiah Keperawatan, 2025)
Background The discomfort felt by pregnant women with a prevalence of 68% is back pain. If not addressed immediately, it will have a negative impact and interfere with the activities of pregnant women. Warm compresses are beneficial for improving blood circulation and reducing aches or pains.Purpose of this study is known the effect of giving warm compresses on the reduction of back pain in pregnant women in the third trimester in the working area of the Paceda Health Center. Methods uses a quasi-experimental design with a one-group pre-post test research design. The sample was taken based on the number of respondents as many as 17 pregnant women in the third trimester using purposive samples. Data collection was carried out using the NRS pain observation sheet (numeric rating scale). Furthermore, the collected data was processed using the help of the SPSS program computer to be analyzed by the Wilcoxon test with a significance level (?) of ? 0.05. Result showed that a decrease in the scale of mild pain was obtained in this study as many as 15 respondents (88.2%). From the results of the Wilcoxon test, a p value = 0.000 was obtained with a significant ? 0.05 which means that Ho was rejected and Ha was accepted. Conclusion of this study is that there is an effect of giving warm compresses on the reduction of back pain in pregnant women in the third trimester in the working area of the Paceda Health Center Bitung City. It is hoped that the Paceda Health Center will provide education to pregnant women on how to overcome back pain with warm compresses.